NITRITE REMOVAL FROM MARINE AQUACULTURE WASTEWATER USING ELECTROCHEMICAL PROCESS - Saleem, M. (The Nucleus, 2010)
The hazardous and toxic nature of some of the constituent such as nitrite in the aquaculture wastewater is of major concern. Present study focuses the removal of nitrite from the aquaculture wastewater prior to disposal. Effect of certain operational parameters such as electrode material, current density, initial pH, and electrode spacing on nitrite removal from aquaculture wastewater was elucidated. Better nitrite removal efficiency achieved when nickel used as compared to stainless steel, graphite and aluminum electrodes. Nitrite removal is positively related to the current density however, increase is up to 31.4% when current density increased from 2.5 to 9.3 mA/cm2 . Further increase in current density does not improve the process efficiency. Removal efficiency of electrochemical process decreased with the increase in initial pH of test solution. However, with the passage of time this difference is diminishing. This may be attributed to the presence of higher amount of hypochloric acid which does not dissociate at lower pH values. Subsequently faster oxidation of nitrite achieved during first few minutes of test runs. Amount of available hypochloric acid reduced at high pH values and oxidation of nitrite reduced subsequently. Rate of nitrite removal found to be increased as the inter-electrode spacing decreased up to an optimal spacing of 3 cm which showed highest nitrite removal. Further reduction in spacing does not augment the removal efficiency probably due to the formation of scale on cathode surface and passivation of electrode which suppressed further oxidation process.